Multi-channel photonic bandgap engineering in hyperbolic graded index materials embedded one-dimensional photonic crystals. (September 2020) - Singh, Bipin K.; Bambole, Vaishali; Rastogi, Vipul; Pandey, Praveen C.
Highlights: Structuring of hyperbolic graded index materials in the form of 1-D PC have investigated. Study the effect of graded materials on multi-channel PBG sensing performances. Number of PBG sensing channels increases with increasing the layer thickness. Operational frequencies of PBG channels can be tuned by changing grading parameters. Proposed GPCs can be implemented to design multi-channel PBG sensors/filters. Abstract: Engineering of multi-channel photonic band gap sensing consequences has been demonstrated in hyperbolic graded index materials embedded one-dimensional (1-D) photonic crystal (PC) in the frequency 150–850 THz region. The multi-channel photonic band gap sensing properties have been investigated by taking into account the reflection and photonic band gap (PBG) spectra of the proposed PC structures. For quarter-wave stacking, we obtain single optical reflection band for band region 646.8 – 434.3 THz with the constituted normal layer refractive index 1.5. Band regions and bandwidths of the single PBG channel can be modulated by changing the refractive index of the constituted normal layer and grading parameter of the hyperbolic graded layer. The number of photonic bands increases with increasing the layer thickness of the GPC structures and leads to work as multi-channel PBG sensors. The operation frequency of the multi-channel PBG sensors can also be tuned by changing the constituted normal layer and grading parameter of the hyperbolic graded layer. These properties lead to design the tunable multi-channel optical sensors/filters engineering. Moreover, the demonstration of the reflection phase shift, group velocity, group delay, and electric field distributions shows the effect of hyperbolic graded index materials on the propagation of light in 1-D PCs. With the engineering of tunable PBGs and structure controllability, hyperbolic graded index materials embedded 1-D PCs provide a promising way to fabricate tunable optical reflectors and multi-channel optical sensors/filters for future optical devices.